Synthesis and characterization of phosphine stabilized mono- and bimetallic Au and Cu nanoparticles and their evaluation as catalysts in 4-Nitrophenol reduction - Matinise, Nonkosi (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.